2020
DOI: 10.5740/jaoacint.19-0240
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh-Performance Hydrophilic Interaction Liquid Chromatography with Tandem Mass Spectrometry Method for the Determination of Paralytic Shellfish Toxins and Tetrodotoxin in Mussels, Oysters, Clams, Cockles, and Scallops: Collaborative Study

Abstract: Background: An ultrahigh-performance LC (UHPLC)–tandem MS (MS/MS) method for determination of paralytic shellfish poisoning toxins and tetrodotoxin (TTX) in bivalve molluscs was developed. To be used for regulatory testing, it needed to be validated through collaborative study. Objective: The aim was to conduct a collaborative study with 21 laboratories, using results to assess method performance. Methods: Study materials incorporated shellfish species mussels, oysters, cockles, scallops, and clams and were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 1 publication
0
51
0
Order By: Relevance
“…Since for both these methods, the concentration factor associated with sample preparation was similar to our method, the difference in sensitivity is due to the performance of the instruments used. An inter-laboratory validation of the HILIC-MS/MS method for the analysis of toxins belonging to the saxitoxin group (PSP), and of TTX in bivalve molluscs, conducted by Turner et al, demonstrated the wide range of sensitivity of MS instrument models [23]. The system used in the present work was classified in the "medium sensitivity" group, whereas the instruments used the above-mentioned studies belonged to the "high sensitivity" group.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Since for both these methods, the concentration factor associated with sample preparation was similar to our method, the difference in sensitivity is due to the performance of the instruments used. An inter-laboratory validation of the HILIC-MS/MS method for the analysis of toxins belonging to the saxitoxin group (PSP), and of TTX in bivalve molluscs, conducted by Turner et al, demonstrated the wide range of sensitivity of MS instrument models [23]. The system used in the present work was classified in the "medium sensitivity" group, whereas the instruments used the above-mentioned studies belonged to the "high sensitivity" group.…”
Section: Discussionmentioning
confidence: 65%
“…For bivalve molluscs, recoveries ranged from 99 to 108%. To the best of our knowledge, the trueness of this method is the best among all in-house-validated procedures [8,16,20,21,23,24]. For gastropods, recoveries ranged from 74 to 80%.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The presence of toxins in benthic invertebrates that may be washed ashore has societal implications, with beach scavenged crabs and starfish implicated in recent canine deaths [ 42 ]. Anecdotally A. diaphanum was found among the stomach contents of a dog that had died following a beach walk in 2005 (pers.comm [ 114 ]) and implicated in multiple dog deaths in 2006 [ 115 ], however, in neither case were PSTs tested for and no archived samples were stored for retrospective analysis. Consequently, further studies on the spatial, temporal and taxonomic patterns in toxins in benthic invertebrates, especially those that are known to be washed ashore after periods of disturbance, could usefully be undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple methods for PSTs have been utilized in recent decades, namely, the mouse bioassay (Association of Official Analytical Chemists (AOAC) method 959.08), the receptor binding assay (AOAC method 2011.27) [55], the pre-column (AOAC method 2005.06) [56] and post-column (AOAC method 2011.02) [57] AOAC certified methods for PSTs, and the internationally validated LC-MS/MS method [58], as well as other mass spectrometric methods reported in the literature [59]; multiple ELISAs for both neosaxitoxin and STX PST analogs have also been developed [60].…”
Section: Introductionmentioning
confidence: 99%